Ba5CdGa6Se15, a congruently-melting infrared nonlinear optical material with strong SHG response. Issue 5 (17th January 2017) - Yin, Wenlong; Iyer, Abishek K.; Li, Chao; Yao, Jiyong; Mar, Arthur
Abstract : Substitution of Cd for Ga leads to partial ordering and opens a band gap in Ba5 CdGa6 Se15, built of corner-sharing tetrahedra. Abstract : The quaternary selenide Ba5 CdGa6 Se15 was prepared by reaction of BaSe and CdGa2 Se4 at 1273 K and forms as light yellow crystals. It adopts a noncentrosymmetric structure (orthorhombic, space group Ama 2, Z = 4, a = 24.2458(8) Å, b = 19.1582(7) Å, c = 6.6028(2) Å) featuring a three-dimensional anionic framework built up of corner-sharing tetrahedra centred by Cd and Ga atoms, with the intervening voids filled by Ba cations. The Cd atoms are partially disordered with Ga atoms within two out of five possible sites; the site preference can be understood in terms of optimizing bond valence sums. Band structure calculations predict that Ba5 CdGa6 Se15 should be a semiconductor in which substitution of Cd for Ga atoms reduces the electron count in a hypothetical all-Ga compound "Ba5 Ga7 Se15 " so that the Fermi level falls within a band gap. Ba5 CdGa6 Se15 is a potential new infrared nonlinear optical material with several attractive properties. First, the large band gap of 2.60(2) eV, as determined from the UV-vis-NIR optical absorption spectrum, implies a high laser damage threshold. Second, strong second harmonic generation signals were observed from nonlinear optical measurements on powder samples, with intensities comparable to that of the benchmark material AgGaS2 ; type-I phase-matching behaviour was confirmed using 2090 nm as the fundamental laser wavelength. Third, this compound melts congruently at a relative low temperature of 866 °C, which could facilitate growth of large crystals eventually required for applications.